Forced degradation studies of ivabradine and in silico toxicology predictions for its new designated impurities - Piotr ePikul; Marzena eJamrógiewicz; Joanna eNowakowska; Weronika eHewelt-Belka; Weronika eHewelt-Belka; Krzesimir eCiura (Frontiers Media S.A., 2016)
All activities aim to eliminate genotoxic impurities or/and protect the medicinal compounds against degradation. There is a need to monitor impurities from all classification groups, so that ivabradine forced degradation studies were performed. Ivabradine proved to be a quite durable active substance, but still new and not known particularly. Increasing temperature, acid, base, oxidation reagent and light cause its degradation. Thirteen degradation products were determined with the usage of HPLC equipped with Q-TOF-MS detector. Six of them, which the most probable structures managed to establish, were selected to ADME/Tox calculations for prediction studies of their pharmacological and toxicological properties. Target prediction algorithm was applied on the basis of Hyperpolarization-activated cyclic nucleotide-gated cation channels as well as more general parameters like logP and aqueous solubility. Ames test and five cytochromes activities were calculated for toxicity assessment of selected degradation products. Pharmacological activity of photodegradation product (UV4) that is known as active metabolite was qualified and identified. Two other degradation compounds (Ox1 and N1) which were formed during degradation process were found to be pharmacologically active with high probability.